Analysis of Tax Crimes Committed by Tax Personnel in Lampung Province - Zainudin Hasan; Simanjuntak, Abelia Duta; Monica (HM Publisher, 2023)
Criminal acts in the field of taxation refer to violations or crimes related to the tax provisions of a country. Tax crime often involve manipulation or violation of the law by individuals in order to avoid or reduce the tax obligations they should pay. This study aimed to analyze tax crimes committed by unscrupulous tax personnel in Lampung province. This research is a qualitative observational study and uses a literature study. Secondary data such as laws and regulations, legal theory, and doctrine are used to explain legal phenomena. This study highlights the phenomenon of tax crime in the Bengkulu and Lampung DGT areas. There are five suspects in tax crimes during 2021. In addition, there is also an investigation into the alleged criminal act of garbage retribution corruption at the Bandarlampung Environment Agency (DLH) for the 2019, 2020, and 2021 fiscal years. The legal basis used in settlement of criminal acts in the field of taxation is Law Number 6 of 1983 concerning general provisions and tax procedures and their amendments. In addition, the norms of criminal acts in the field of taxation also include provisions contained in the Criminal Code and other laws and regulations. In conclusion, corruption is an act of enriching oneself or others, which can harm the economy and state finances. Legal subjects of corruption can be corporations and civil servants.